Construction and construction education and training in the muslim world - a preliminary assessment and policy implication - Abdul Rashid, Khairuddin; Abdul Mohit, M.; Preece, Christopher Nigel (2009)
This paper reports on two preliminary examinations, namely on; (i) the size and contribution of the construction sectors of the countries of the Muslim world to their respective economies; and (ii) state of their construction education and training. Key results of the preliminary examinations include: (i) majority of the construction sectors of the countries of the Muslim world make small contribution to their GDPs; (ii) at per capita level, most of the countries of the Muslim worlds' construction GDPs are very small; (iii) per capita construction GDP is positively correlated to per capita GDP and GDP from the industrial sector but is negatively related to other sectoral GDPs; (iv) countries of the Muslim world suffer constraints in the availability of indigenous semi-skilled and skilled workers, semi-professionals and professionals in all fields related to construction; (v) higher education and training in the Muslim world generally lag far behind those of the developed countries; and (vi) among the countries of the Muslim world Malaysia appears to be among the very few Muslim countries that offer world class education and training including education and training in construction.